2013
DOI: 10.1007/s10554-013-0342-3
|View full text |Cite
|
Sign up to set email alerts
|

Divergent determinants of 18F–NaF uptake and visible calcium deposition in large arteries: relationship with Framingham risk score

Abstract: To compare regional vascular distribution and biological determinants of visible calcium load, as assessed by computed tomography, as well as of molecular calcium deposition as assessed by (18)F-NaF positron emission tomography. Eighty oncologic patients undergoing (18)F-NaF PET/CT scan were included in the study. Cardiovascular-risk stratification was performed according to a simplified version of the Framingham model [including age, diabetes, smoking, systolic blood pressure and body mass index (BMI)]. Arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 29 publications
6
34
0
Order By: Relevance
“…The study included 64 patients with either breast or prostate cancer (14 men and 50 women; mean age, 65.3 6 8.2 y; range, 26-81 y) undergoing 18 F-NaF PET/CT to evaluate for the presence of bone metastases. To be included in the study, the patient had to have at least one calcification in the infrarenal abdominal aorta.…”
Section: Patientsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study included 64 patients with either breast or prostate cancer (14 men and 50 women; mean age, 65.3 6 8.2 y; range, 26-81 y) undergoing 18 F-NaF PET/CT to evaluate for the presence of bone metastases. To be included in the study, the patient had to have at least one calcification in the infrarenal abdominal aorta.…”
Section: Patientsmentioning
confidence: 99%
“…Calcification was defined as a mural area having a minimum density of 130 HU (14). Patients were excluded from the study if they had a history of vasculitis, autoimmune disease, or systemic inflammatory disease or had received chemotherapy or radiotherapy in the preceding 8 wk, as previously proposed (18). Ongoing or previous statin treatment was a further exclusion criterion to exclude the influence of these drugs on the results (19).…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten‐year Framingham risk scores for CVD and death are related to 18 F‐NaF uptake 64. Other retrospective studies have shown positive correlations between arterial 18 F‐NaF uptake and CVD risk factors, including age, sex, hypertension, hypercholesterolemia, and diabetes mellitus, further supporting the notion that 18 F‐NaF PET imaging may improve CVD risk stratification 98, 100, 101, 102, 104, 111, 112, 113, 114…”
Section: Positron Emission Tomographymentioning
confidence: 80%